2017
DOI: 10.1080/20008198.2018.1503522
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged grief symptomatology following violent loss: the mediating role of meaning

Abstract: Background: Prolonged Grief Disorder (PGD) is over-represented among those who have lost loved ones to violent causes. To tailor PGD interventions for this vulnerable population it is critical to examine the aetiology of PGD specifically in the context of violent death bereavement. Previous studies have suggested that violent loss increases symptoms of PGD by hindering the mourner’s ability to make meaning of the death or its aftermath. However, these studies have relied on cross sectional data that preclude g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 74 publications
2
18
0
3
Order By: Relevance
“…Milman et al ( 2018 ) examined whether violent loss increases symptoms of PGD by hindering the bereaved person’s ability to make meaning of the death. In a prospective, longitudinal sample of 171 violently bereft persons, sense of peace and continuing bonds served as mediators.…”
Section: Overview Of This Special Issuementioning
confidence: 99%
“…Milman et al ( 2018 ) examined whether violent loss increases symptoms of PGD by hindering the bereaved person’s ability to make meaning of the death. In a prospective, longitudinal sample of 171 violently bereft persons, sense of peace and continuing bonds served as mediators.…”
Section: Overview Of This Special Issuementioning
confidence: 99%
“…Building on previous research that demonstrated the mediating role of meaning‐making in the etiology of PGD (Currier, Holland, & Neimeyer, ; Milman et al, ; Rozalski et al, ), the present study is the first to provide evidence indicating that rumination moderates this mediating pathway. Among participants who reported higher levels of rumination, the degree of meaning made early in grief predicted symptoms of PGD more strongly 7–10 months later.…”
Section: Discussionmentioning
confidence: 53%
“…Previous research has made a compelling case for the central role of meaning in the etiology of PGD symptomatology, suggesting that risk factors increase symptoms of PGD by hindering meaning making such that the bereft are unable to “make sense” of the death or its aftermath in their ongoing lives (Currier, Holland, Coleman, & Neimeyer, ; Lichtenthal, Neimeyer, Currier, Roberts, & Jordan, ; Milman et al, ; Rozalski, Holland, & Neimeyer, ). Such research provides an empirical basis for facilitating meaning making among at‐risk grievers as a clinical approach for effectively intervening in the development of PGD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 An expansive understanding of what sense-making entails links with research on the significance of meaning as a mediator for complicated or prolonged grief. 23 This may partially answer concerns expressed by Christiaans, 24 who drew attention to the lack of understanding of the cause of death in surviving relatives even in the face of an established cause, which undermined uptake of genetic counselling by some family members. For family members in our study, meaning-making included understanding the impact of the death on their sense of self and their place in the world.…”
Section: Discussionmentioning
confidence: 99%